Proteome and metabolome alterations in heart and liver indicate compromised energy production during sepsis - Hinkelbein, Jochen; Kalenka, Armin; Schubert, Charlotte; Peterka, Anna; Feldmann, Robert Enrico (Protein and peptide letters, 2010)
During the course of sepsis, heart and liver dysfunction occurs in 20-30 % of patients. Both septic cardiomyopathy and septic liver dysfunction have a high mortality and the underlying molecular pathophysiology remains unclear. The present study investigated changes in both cardiac and liver protein expression after cecal ligature and puncture (CLP) in a model of rat sepsis during a post-induction time course of 12, 24, and 48 hours. After approval by the local institutional review board, 62 male Wistar rats were investigated and assigned to three sham groups (n=16) and three sepsis groups (n=46). Rats of the sepsis groups and control groups were analyzed at specific time points after sepsis induction. Sepsis was induced by CLP and both heart and liver were removed after decapitation and prepared for proteomics. 2D-gel electrophoresis (2D-GE) and mass spectrometry (MS) as well as bioinformatic network pathway analysis (Ingenuity Pathways Analysis, IPA) were used to identify changes in protein expression between septic and non-septic samples. N=27 rats of the sepsis group died (mortality 59 %) and no rat of the sham group died. More than 1,100 proteins could be discriminated with the proteomic method in both organs, of which 12 and 13 proteins were significantly regulated in heart and liver, respectively. 82 % of the cardiac proteins could be associated with mitochondrial function. Both heart and liver proteins were primarily down-regulated in the course of sepsis. IPA associated the sets of differentially regulated proteins with proteins of heart and liver with compromised energy production. Sepsis induced significant alterations in the cardiac and liver proteome at 12, 24, and 48 hours after sepsis induction. Differentially regulated proteins of both organs mainly play a role in energy production. The diverse protein regulation indicates metabolic derangement and severely compromised cellular energy production following sepsis. Here, protein alterations may reflect septic organ dysfunction.